2009
DOI: 10.1259/bjr/26005109
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery duplication and aneurysms: 64-slice multidetector CT findings

Abstract: Duplication of vertebral artery is a very rare finding. Here, we present a case of vertebral artery duplication, cervical vertebral artery aneurysm and multiple intracranial aneurysms in a 59-year-old woman. This is the first case of vertebral artery duplication with cervical vertebral artery and intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…[4] But it is also reported that the altered hemodynamics of the anomalous origin may predispose a patient to certain cerebrovascular pathologies like aneurysm and dissection. [56789] We report here an incidental observation of bilateral duplication of the V-1 segment of the vertebral artery and to the best of our knowledge this is the third such case to be reported.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…[4] But it is also reported that the altered hemodynamics of the anomalous origin may predispose a patient to certain cerebrovascular pathologies like aneurysm and dissection. [56789] We report here an incidental observation of bilateral duplication of the V-1 segment of the vertebral artery and to the best of our knowledge this is the third such case to be reported.…”
Section: Introductionmentioning
confidence: 76%
“…[567891718] It has been proposed that distinct histological features of the two limbs of the duplicated VA may result in altered hemodynamics, but no such evidence was found in a cadaveric study on RVA duplication. [19]…”
Section: Discussionmentioning
confidence: 99%
“…One of the rarest anomalies is the duplication of the extracranial segments of vertebral arteries, which is usually an incidental finding in an autopsy series, angiographic studies or, more recently, MR and CT angiography and color Doppler studies (Harnier et al 2008; Ionete and Omojola 2006; Kendi and Brace 2009; Mahmutyazicioglu et al 1998). …”
Section: Introductionmentioning
confidence: 99%
“…The term "fenestration" refers to two parallel segments of the VA with a single origin, while the term "duplication" refers to a VA that has two origins with fusion at various levels in the neck (5,6).…”
Section: Discussionmentioning
confidence: 99%